Orthodontic treatment time: can it be shortened? - Ricardo Moresca
Abstract Introduction: In the literature, no consensus has been reached about orthodontic treatment time. Similarly, the determining factors of the latter have not yet been completely elucidated. Objective: The aim of the present article was to deepen the discussion on the major factors influencing orthodontic treatment time, as well as to present some strategies that have proven effective in controlling and shortening it. Method: Based on evidences found in the literature, the method focussed in providing the basis for clinical decision-making. Conclusions: Treatment time varies according to the type of malocclusion and treatment options. Orthodontist's influence, patient's characteristics and compliance are all decisive in determining treatment time, while the effects provided by orthodontic appliances and methods used to speed tooth movement up seem little effective.